Blue light‐emitting diodes induce autophagy in colon cancer cells by Opsin 3. Issue 2 (11th January 2018) - Yoshimoto, Toshiaki; Morine, Yuji; Takasu, Chie; Feng, Rui; Ikemoto, Tetsuya; Yoshikawa, Kozo; Iwahashi, Syuichi; Saito, Yu; Kashihara, Hideya; Akutagawa, Masatake; Emoto, Takahiro; Kinouchi, Yosuke; et al.
Abstract: Background: Light emitting‐diodes (LED) have various effects on living organisms and recent studies have shown the efficacy of visible light irradiation from LED for anticancer therapies. However, the mechanism of LED's effects on cancer cells remains unclear. The aim of the present study was to investigate the effects of LED on colon cancer cell lines and the role of photoreceptor Opsin 3 (Opn3) on LED irradiation in vitro. Methods: Human colon cancer cells (HT‐29 or HCT‐116) were seeded onto laboratory dishes and irradiated with 465‐nm LED at 30 mW/cm 2 for 30 minutes. Cell Counting Kit‐8 was used to measure cell viability, and apoptosis and caspase 3/8 expression were evaluated by AnnexinV/PI and reverse transcription‐polymerase chain reaction (RT‐PCR), respectively. Autophagy and expression of LC‐3 and beclin‐1 were also evaluated by autophagy assays, RT‐PCR and Western blotting. We further tested Opn3 knockdown by Opn3 siRNA and the Gi/o G‐protein inhibitor NF023 in these assays. Results: Viability of HT‐29 and HCT‐116 cells was lower in 465‐nm LED‐irradiated cultures than in control cultures. LC‐3 and beclin‐1 expressions were significantly higher in LED‐irradiated cultures, and autophagosomes were detected in irradiated cells. The reductive effect of cancer cell viability following blue LED irradiation was reversed by Opn3 knockdown or NF023 treatment. Furthermore, increased LC‐3 and beclin‐1 expression that resulted from blue LED irradiation was suppressed by Opn3 knockdown or NF023 treatment. Conclusion: Blue LED irradiation suppressed the growth of colon cancer cells and Opn3 may play an important role as a photoreceptor. Abstract : Light‐emitting diode (LED) irradiation at 465 nm induced autophagy in colon cancer cell lines. LED (465 nm) irradiation‐induced autophagy was reversed by Opsin 3 (Opn3) knockdown or NF023 treatment. LED (465 nm) irradiation suppressed the growth of colon cancer cells by inducing autophagy by Opn3.